Immunization with Toxoplasma gondii GRA17 deletion mutant induces partial protection and survival in challenged mice - Wang, Jin-Lei; Elsheikha, Hany M.; Zhu, Wei-Ning; Chen, Kai; Li, Ting-Ting; Yue, Dong-Mei; Zhang, Xiao-Xuan; Huang, Si-Yang; Zhu, Xing-Quan (Frontiers Media, 2017)
Toxoplasmosis remains a world-threatening disease largely because of the lack of a fully effective vaccine. Here, we created a ΔGRA17 mutant by disrupting the virulence factor GRA17 using CRISPR-Cas9 method. Then, we tested whether ΔGRA17 tachyzoites can be used as a live-attenuated vaccine against acute, chronic, and congenital Toxoplasma gondii infection in mice. Immune response evoked by ΔGRA17 immunization suggested a sequential Th1 and Th2 T cell response, indicated by high levels of Th1 and a mixed Th1/Th2 cytokines at 28 and 70 days after immunization, respectively. ΔGRA17-mediated immunity fully protected mice against lethal infection with wild-type (wt) RH strain, heterologous challenge with PYS, and TgC7 strains of the Chinese ToxoDB#9 genotype, and T. gondii Pru strain. Although parasite cysts were detected in 8 out of 10 immunized mice, cyst burden in the brain was significantly reduced (P < 0.05) in immunized mice (53 ± 15 cysts/brain) compared to non-immunized mice (4,296 ± 687 cysts/brain). In respect to congenital infection, the litter size, survival rate, and body weight (BW) of pups born to ΔGRA17-immunized dams were not different compared to pups born to naïve control dams (P = 0.24). However, a marked reduction in the litter size (P < 0.001), survival rate, and BW (P < 0.01) of pups born to non-immunized and infected dams was detected. Also, immunized dams infected with type II Pru strain had significantly (P < 0.001) less cyst burden in the brain compared with non-immunized and infected dams. These findings show that immunization with ΔGRA17 strain evokes cell-mediated and neutralizing antibody responses and confers some degree of protection against challenge with homologous and heterologous virulent T. gondii strains.